Diterminan Debt Maturity Structure Perusahaan Consumer Goods Yang Terdaftar di ISSI Periode 2012-2015 - Gianissa Pandu Islamy (Dept. Ekonomi Syariah FEB Unair, 2018)
This research analyzes the influence of firm size, profitability, tangibility, and asset maturity variable to debt maturity structure of consumer goods company in Indonesia. The population of this study consists of companies of industrial goods and consumption listed in Indonesia Sharia Stock Index period 2012-2014. The sample was taken by using purposive sampling method so that obtained 19 companies that fulfill the requirement as a sample. The result of research with Fixed Effect estimation model shows that firm size, profitability, and asset maturity have significant effect to debt maturity structure with a different level of significance. Based on the value of the coefficient of determination (R2) of 92.06% shows that the percentage of the ability of exogenous variables in explaining endogenous variables of 92.06% while the rest of 7.94% explained by other variables outside this study.